2014
DOI: 10.1038/sj.bdj.2014.1000
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement: Oral health and elite sport performance

Abstract: Our purpose with this consensus statement is a call to action regarding oral health in sport since there is no evidence of an improving situation. As background, this paper will first summarise the key issues; what we know about oral health in elite sport, the impact of oral health on performance, how oral health might affect performance, why athletes have poor oral health and evidence-based oral health promotion and disease prevention. It will then conclude with recommendations to guide the improvement of ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 40 publications
4
68
1
9
Order By: Relevance
“…Since more than 90% of each senior squad participated in the study, we can be confident that the results represent a true picture. These findings are also consistent with data we collected during the London 2012 Olympic Games and a recent systematic review 2. The emerging picture is of poor oral health in elite sport with important self-reported impacts on self-reported performance.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Since more than 90% of each senior squad participated in the study, we can be confident that the results represent a true picture. These findings are also consistent with data we collected during the London 2012 Olympic Games and a recent systematic review 2. The emerging picture is of poor oral health in elite sport with important self-reported impacts on self-reported performance.…”
supporting
confidence: 91%
“…As some challenges to oral health such as carbohydrate-containing sport supplements may be unavoidable for professional athletes, we recommend a strategy of disease prevention and risk mitigation 2 4. These measures include:

Using of higher concentration fluoride toothpastes (2800 and 5000 ppm fluoride) and mouthrinses;

Avoiding carbohydrate when not required for performance;

Effective daily oral hygiene, particularly between the teeth.

…”
Section: Universal Prevention Strategy Versus a Targeted Approachmentioning
confidence: 99%
“…The causes of poor oral health include nutrition,18 19 unfavourable individual health behaviours,20 cultural norms and structural determinants such as access to oral health promotion and value of oral health within sport support system 4. Notably, more than three-quarters of participants reported attendance at a dentist for a check-up within 12 months, and this is corroborated anecdotally by the participating dentists.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, a systematic review of professional and elite sport from our group has shown similar findings across a wide range of sports 2. These findings have led to the development of position/consensus statements with recommendations to promote oral health and related research as part of sport and exercise medicine 3 4…”
Section: Introductionmentioning
confidence: 85%
“…gingivitis, periodontitis), which, according to athletes, have impact on their quality of life, confidence, training and performance, and may have long-term consequences [10][11][12] . Experimental intervention studies prove that health promotion programmes, oriented towards the Salutogenesis approach, enable elite athletes to acquire knowledge and skills for coping with overuse injuries [13][14][15] and development of health management strategies 16 , which lead to suitable relaxation of stress and performance enhancement in elite sport training and competitions 17 .…”
Section: Introductionmentioning
confidence: 99%